Incidencia del plan operativo anual (poa) en la gestión escolar de la Escuela “Once de Noviembre”, parroquia Ignacio Flores, de la ciudad de Latacunga en el año lectivo 2014-2015 - Changalombo Saquinga, Byron Rodrigo (2015)
The research is focused on the incidence of the Annual Operating Plan in school management, as it is an important issue to development of the institution, since the Annual Operating Plan is an instrument is within the Institucional Education Project, it permits to the institutions to integrate and guide the implementation of activities under this instrument, determined by the educative unit, where the objectives and goals outlined in the short and medium terms are met. Therefore it is based on management to achieve concrete actions through planning where the purposes and processes needed to check the quality of education will be achieved. This study has identified the situation in the school, therefore is necessary to develop educational proses thought the Annual Operating Plan to meet efforts efficiently and effectively facilitating greater understanding and flexible educational work to entire educational conglomerate as well as the socialization at managers must become a hub for fully compliance activities presented within the Institutional Education Project.